Perioperative management of adult patients undergoing coronary artery bypass grafting and valve surgery: a literature review - Nair Naiara Barros de Vasconcelos; Veronica Neves Fialho Queiroz; Guilherme Martins de Souza; Sandrigo Mangini; Fernando Morita Fernandes Silva; Luiz Guilherme Villares da Costa; Pedro Paulo Zanella do Amaral Campos; Samuel Padovani Steffen; Flávio Takaoka; Ary Serpa Neto; Adriano José Pereira; Carmen Silvia Valente Barbas; et al. (Einstein (São Paulo))
ABSTRACT Purpose of review Coronary artery bypass grafting, revascularization by percutaneous coronary intervention, and heart valve surgery are crucial therapeutic interventions for patients with various cardiovascular diseases. The objective of this literature review was to present the main evidence and practical aspects of the perioperative management of patients undergoing coronary artery bypass grafting and heart valve surgery. Recent findings Despite advancements in surgical and anesthetic techniques, coronary artery bypass grafting and heart valve surgery present significant risks for perioperative complications and death. These complications increase morbidity, mortality, and length of hospital stay. Coronary artery bypass grafting is indicated for patients with significant left main or advanced coronary artery disease. Most patients undergoing coronary artery bypass grafting with a reasonable life expectancy are advised to adopt a multiple-arterial graft strategy using two or three arterial grafts. Revascularization by percutaneous coronary intervention is frequently performed to alleviate symptoms in patients with stable angina and coronary artery stenoses causing moderate or severe ischemia. Intraoperative coagulation management should include tranexamic acid after the induction of anesthesia and protamine immediately after the termination of extracorporeal circulation. The prophylactic use of fresh-frozen plasma, desmopressin, recombinant activated factor VII, or fibrinogen to reduce bleeding is not recommended. Inhaled anesthetics have recognized cardioprotective properties; however, it is unclear whether anesthesia with a volatile agent can reduce mortality in patients undergoing elective surgery. Echocardiography plays an important role in the perioperative management of patients by defining myocardial structure, assessing intracardiac blood flow, aiding preoperative evaluation, facilitating intraoperative monitoring, and providing real-time guidance for intervention. The perioperative management of patients undergoing coronary artery bypass grafting, percutaneous coronary intervention, and heart valve surgery is highly complex and involves numerous specific conditions. Effective management requires dedicated multidisciplinary teams skilled in timely recognition, prevention, and treatment to ensure appropriate care.